Incidence of Mycoplasma gallisepticum and Mycoplasma synoviae in broiler flocks at the Federal District of Brazil and its surrounding areas - Santos, Milena Mendonça dos; Nascimento, Elmiro Rosendo do; Barreto, Maria Lúcia; Gonçalves, Vitor Salvador Picão; Santana, Ângela Patrícia (Semina: Ciências Agrárias, 2021)
Mycoplasma is an important avian pathogen that can cause both respiratory disease and synovitis in birds, resulting in considerable economic losses to the poultry industry worldwide. This study aimed to determine the incidence of Mycoplasma gallisepticum and M. synoviae in broiler flocks at the Federal District and its surrounding regions using polymerase chain reaction (PCR). All slaughtered lots (57 flocks) were analyzed from July to November in one of the two slaughterhouses at the Federal District with Federal inspection services. Approximately 10 samples of broiler tracheae per slaughtered batch were collected from the evisceration line. The results obtained from the accumulated incidence over the study period were 7.02% and 35.09% for M. gallisepticum and M. synoviae, respectively. A greater concentration of flocks affected by M. synoviae was observed during October. The sample design as well as the PCR technique assisted in detecting both agents in the broiler batches in the first epidemiological study of these two agents in the region.